Dynamics of the Korean population since 1960 and its relationship with the demographic transition (2016)
The demographic transition process in the Republic of Korea, where the high mortality rates that remained until the years after the war decreased significantly, followed by the reduction of fertility rates, was shaping the dynamics and distribution of its population, which underwent a process of expansion and subsequent aging. This article describes the main changes in the dynamics of the Korean population since the 1960s (the decade in which large-scale family planning programs began to be implemented, as part of the economic development policies of the five-year plans ); identifying two main characteristics of the demographic transition: changes in population distribution and population aging.